PENGARUH WAKTU STABILISASI PADA SEQUENCING BATCH REACTOR AEROB TERHADAP PENURUNAN KARBON - Sumiyati, Sri (Universitas Diponegoro, 2006)
One of biological wastewater treatment process modification Sequencing Batch Reactor by exploiting period of stabilization time earn to lessen capacities of total aeration volume. Mechanism that happened in this SBR modification same as that happened in Contact Stabilization. There was existence process biosorption, was due to adsorption of the organic matter onto sludge particels, during the contact period (fill - react time).This research aim to know influence of stabilization time to degradation of COD. This research, used SBR reactor with volume operate for 5 Liter with COD influent consentration 1139.2 mg/L. The variation of stabilization time : 3, 4, 5 and 6 hours and time reacted : 0,5 ; 1 ; 1,5 and 2 hours as independent variables. COD effluent concentration as depended variable.Result of research indicate that progressively time of stabilization and concentration COD (mg/L) will experience of efficiency improvement. Time reacted to give influence the happening of biosorption (the adsorption of organic matter onto sludge particel). The fenomena that happened is degradation of concentration COD will achieve maximum level at the total contact time 1,5 hour. Efficiency of optimum degradation COD become of variation r/s = 1 : 6.